Pengembangan Manajemen Strategi Kepala Madrasah dalam Peningkatan Mutu Pendidikan Madrasah Swasta di MA Al-istiqomah Kota Sukabumi - M. Alwi AF (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study aims to explore how the strategic management implemented by the Head of Madrasah at MA Al-Istiqomah, Sukabumi, can improve the quality of education in private madrasas. The research methodology used is a qualitative approach with a case study design, involving interviews, observations, and documentation from the head of the madrasa, teachers, and several students. The strategic management practices investigated include the formulation of vision and mission, development of strategic plans, transformational leadership, and effective resource management. The results of the study indicate that improvement in education quality at this institution can be achieved through fostering good relationships between teachers and staff, creating a conducive school environment, and enhancing overall performance. Key findings highlight that the strategic initiatives led by the head of the madrasa, such as regular monitoring and evaluation, and the inclusion of all stakeholders in the planning process, play a critical role in achieving educational objectives. These findings suggest that effective strategic management can have a significantly positive impact on the quality of education in private madrasas. The implications of this study emphasize the importance of developing transformational leadership, efficient resource management, and continuous evaluation to achieve higher educational goals and create a sustainable impact on educational outcomes.